Numerical activities of daily living in adults with neurofibromatosis type 1. Issue 11 (29th August 2017) - Burgio, F.; Benavides‐Varela, S.; Arcara, G.; Trevisson, E.; Frizziero, D.; Clementi, M.; Semenza, C.
Abstract: Background: This study aimed to identify the mathematical domains affected in adults with neurofibromatosis 1 (NF1) and the impact of the numerical difficulties on the patients' activities of daily living. Methods: We assessed 28 adult patients with NF1 and 28 healthy control participants. All participants completed the standardised battery of numerical activities of daily living along with clinical batteries of cognitive (Mini‐Mental State Examination) and daily functioning (instrumental activities of daily living). The group comparisons of the performance on numerical activities of daily living were carried out using t ‐test correcting for multiple comparisons. Results: The results showed that the NF1 group performed worse than controls in written subtractions, written multiplication, multiplication principles and digit comprehension (dot counting) tasks. Importantly, no significant differences in numerical ecological tasks were found between patients and controls, suggesting a possible use of compensatory strategies in daily living abilities in spite of calculation deficits. Conclusion: The findings indicate that NF1 affects calculation but not the basic comprehension or representation of numbers in adult patients. These data have important implications for designing cognitive interventions tailored to the cognitive profile of individuals with NF1.